Volatile halocarbon measurements in the marine boundary layer at Cape Point, South Africa. (1st October 2019) - Kuyper, Brett; Lesch, Timothy; Labuschagne, Casper; Martin, Damien; Young, Dickon; Khan, M. Anwar H.; Williams, Alastair G.; O'Doherty, Simon; Davies-Coleman, Michael T.; Shallcross, Dudley E.
Abstract: Volatile organic halocarbons play a significant role in the biogeochemical cycling of halogens in the atmosphere. High frequency, in situ measurements of methyl iodide (CH3 I), bromoform (CHBr3 ), dibromomethane (CH2 Br2 ) and methyl bromide (CH3 Br) were measured in the marine boundary layer at Cape Point, South Africa by an automated Absorption Desorption System-Gas Chromatography-Mass Spectrometer (ADS-GC-MS) between January and November 2017. These are the first multi-halocarbon measurements recorded at Cape Point and represent the longest time series to date. Baseline wind conditions were established using both wind direction and radon ( 222 Rn) concentration as markers of clean air. The baseline mixing ratios observed were 0.61 ± 0.29, 2.02 ± 0.89, 1.08 ± 0.17 and 6.09 ± 0.50 ppt, for CH3 I, CHBr3, CH2 Br2, and CH3 Br, respectively. A statistically significant difference in short-lived halocarbon occurrence was established between anthropogenically affected and clean marine air masses for CH3 Br at the Cape Point site. The CHBr3 and CH2 Br2 mixing ratios were not statistically different (p > 0.05) when comparing the anthropogenically affected and clean marine air masses. The mixing ratios of CH3 I suggested a strong seasonal variation with higher production in austral Summer-Autumn months than in the austral Winter-Spring months. A general chemical decay line was calculated for baseline CH2 Br2 and CHBr3 measurements at Cape Point. An analysis of the ln([CH2 Br2 ]/[CHBr3 ]):ln([CHBr3 ]) ratio for the Cape Point dataset exhibited a slight deflection to the right of the general chemical decay line, suggesting the influence of greater [CHBr3 ]:[CH2 Br2 ] source ratios rather than their dilution. Graphical abstract: Variation of seasonal source strength and distribution of four halocarbons arriving at Cape Point during 2017. Image 1 Highlights: First long-term multi-halocarbon measurements at Cape Point. Significant seasonal and air mass differences were identified for some of the halocarbons. Cape Town air masses have the influence of greater [CHBr3 ]:[CH2 Br2 ] source ratios rather than their dilution.